Enhancing compressive performance of architected hexagonal honeycombs with corrugated stiffeners - Mohammed Ayaz Uddin; Imad Barsoum; Shanmugam Kumar; Andreas Schiffer (Results in Engineering, 2025)
This study explores the impact of incorporating corrugated stiffeners into hexagonal (Hex) honeycombs on their quasi-static compressive behaviour and energy absorption. The effectiveness of this novel design is validated through a comprehensive set of experiments and finite element simulations performed under in-plane and out-of-plane compression. It is demonstrated that the architected hexagonal honeycombs with corrugated stiffeners (AHex) outperform traditional Hex honeycombs of equal weight when subject to in-plane loading along the stiffener direction, reporting maximum enhancements in the elastic modulus, collapse strength and energy absorption of 348 %, 187 % and 112 %. When loaded transverse to the stiffeners or along the out-of-plane direction, the AHex and Hex honeycombs show comparable compressive performance. A finite element-based parametric study further shows that the compressive performance of AHex honeycombs is maximized when the stiffeners are 1.2 times thicker than the hexagonal cell walls and form an internal angle of 155°. The results highlight the potential of corrugated networks in honeycombs to improve compressive performance in preferred directions, expanding their applicability.